Utilization of Islamic Archaeological Sites as a Foundation for the Development of Islamic Tourism in the Communities of Banda Aceh and Aceh Besar: Pemanfaatan Situs Arkeologi Islam Sebagai Landasan Pengembangan Wisata Islami Pada Masyarakat Kota Banda Aceh dan Aceh Besar - Hasanah, Ida; Fitriani, Fitriani; Irwan, Irwan; Fatianda, Septian; Nur, Muhammad; Agustina, Lisa; Arfan, Fahmi; Rumaida, Rumaida; Meutia Maulida, Cutnyak (Indonesian Journal of Islamic History and Culture, 2026)
The development of Islamic tourism in the City of Banda Aceh and Aceh Besar Regency has considerable potential due to the abundance of Islamic archaeological sites distributed throughout the region. However, the utilization of these sites as a foundation for Islamic tourism development has not yet been optimized. This study aims to analyze the utilization of Islamic archaeological sites as a basis for the development of Islamic tourism among communities in Banda Aceh City and Aceh Besar Regency. This research employs a descriptive qualitative approach, with data collected through field observations, in-depth interviews, and documentation of several Islamic archaeological sites, including mosques and burial complexes. The findings indicate that Islamic archaeological sites possess high historical, cultural, and spiritual values and have strong potential to be developed as Islamic tourism attractions through active community involvement, the strengthening of educational functions, and the integration of local cultural values. Nevertheless, challenges remain in terms of site management, accessibility, and coordination among stakeholders. This study is expected to contribute academically to the discourse on the utilization of Islamic archaeological sites and provide practical implications for community-based Islamic tourism development and the preservation of cultural heritage in other regions with similar characteristics